Multiallelic digenic control of vernalization requirement in carrot (Daucus carota L.) - Wohlfeiler Altavilla, Josefina (2019)
Carrots are typically classified as annual or biennial, depending on their vernalization requirement for flowering, a trait that is genetically-conditioned. Wild carrots are predominantly annual, requiring less hours of cold temperatures for flower induction, whereas most cultivated carrots are biennial (i.e., they have higher cold temperature requirements). After vernalization, if followed by long days, floral stem elongation and flowering take place. Previous studies using F2 and BC1 families derived from crosses between an early and a late-flowering line revealed segregation ratios consistent with a monogenic trait, with annual habit being dominant over biennial. In this work, we studied inheritance and segregation of the vernalization requirement in carrot F2 populations derived from crosses involving carrots of different genetic backgrounds and geographical origins. Nine crosses between biennial and annual phenotypes were analyzed, for 2 years, by means of percentage of flowering plants (parental lines, F1 and F2 families were sown in the fall for adequate discrimination between annual and biennial plants). Based on the obtained segregation ratios, a genetic model for this trait was proposed. The results are consistent with a model of two genes (Vrn-A and Vrn-B) with three alleles controlling the vernalization requirement. Dominance of annuality was clear for both genes, with A1 allele having an epistatic effect over Vrn-B. Vrn-A and Vrn-B interact generating different vernalization requirement levels.